The mobile constitution of society : rethinking the mobility-society Nexus - Söderström, Ola (My University, 2010)
Concepts and metaphors referring to the idea of mobility have become pervasive in contemporary social theory. The aim of this article is to discuss what is implied by considering contemporary society as constituted by mobility – or rather mobilitiesi, to use the lexicon of scholars in this field. To do so, we start by reviewing some of the most influential contemporary social theories, and provide an account of the ways in which they handle and operationalize the concept of mobility. In the second part, we critically reflect on the ‘new mobilities paradigm’ by seeking to identify its contributions to social theory, as well as its weaknesses and areas for development. We argue, first, that in order to be constructed as a full-fledged theory, mobility studies need to engage in an ontological discussion regarding the similarities and differences between various mobilities; second, that a more substantial conceptual reflection needs to be led with regard to the mutual constitution of mobility and society. We conclude by proposing an analytical framework intended to overcome these limitations, which we then illustrate through an empirical example regarding the mobility of institutions of higher education.
Keywords: Mobility studies; global flows; social theory